Corruption and Development in Nigeria: A Study of Ondo State - Ejumudo, Kelly Bryan Ovie; Ejumudo, Tobi Becky (Law Research Review Quarterly, 2021)
This study investigates corruption and development in Nigeria using Ondo State as a case study. Four null hypotheses were formulated for the study. The design of the study was a descriptive survey. Three hundred (300) staff were drawn from the six selected ministries using stratified and simple random sampling techniques. The instrument used for data collection was the corruption and development questionnaire. The data were analyzed using chi-square. The findings of the study revealed that there is a significant relationship between corruption and development in the road infrastructure sector in Ondo State. The study also showed that there is a significant relationship between corruption and development in the education sector in Ondo state. The study equally indicated that there is a significant relationship between corruption and development in the agriculture sector in Ondo State. The study also showed that there is a significant relationship between corruption and development in the health sector in Ondo State. The study recommended among others that the Nigerian government should not be selective in its application of the anti-corruption laws as enshrined in the legislation that created the anti-corruption agencies irrespective of the culprit’s stature or position in the society. The study also recommended that there should be a change in the public sector get-rich-quick as well as service mentality and practice in such a way that it will bring about the genuine commitment by the government at all levels to the provision of social services to the citizens.